2019
DOI: 10.1007/s40090-019-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of metal ion-doped CoMgAl-hydrotalcite visible-light-driven photocatalyst

Abstract: Preparation and application of CoMgAl-hydrotalcites have been studied. In this paper CoMgAl-LDHs photocatalysts were prepared by co-precipitation. Various techniques such as UV-visible spectrometry (UV-vis), BET, differential thermal gravimetric analysis, scanning electron microscopy analysis and X-ray diffraction were used to investigate the catalytic activity, structure, and composition of the prepared samples. The photocatalysts were developed as layered double hydroxides (LDHs) due to their layered structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…As can be seen from Figure 8b, the U-LDH 5 thermal decomposition process is divided into three stages [46,47], between 247~300 °C for the first phase of weight loss, which is due to the removal of water from the interlayer and the physical adsorption surface [48]. At this step, U-LDH 5 remained a layered structure.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Figure 8b, the U-LDH 5 thermal decomposition process is divided into three stages [46,47], between 247~300 °C for the first phase of weight loss, which is due to the removal of water from the interlayer and the physical adsorption surface [48]. At this step, U-LDH 5 remained a layered structure.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesized ZnAl–LDH/MOF-5 nanocomposite photocatalyst shows enhanced photocatalytic degradation efficiencies compared to the standard photocatalyst TiO 2 , reported LDH or MOF based photocatalysts, as shown in Table 1. 40–47…”
Section: Resultsmentioning
confidence: 99%
“…The synthesized ZnAl-LDH/MOF-5 nanocomposite photocatalyst shows enhanced photocatalytic degradation efficiencies compared to the standard photocatalyst TiO 2 , reported LDH or MOF based photocatalysts, as shown in Table 1. [40][41][42][43][44][45][46][47] A plausible mechanism of the photocatalytic dye degradation reaction of the anionic dyes by the ZnAl-LDH/MOF-5 nanocomposite is represented in Fig. 11.…”
Section: Dye Removal Studymentioning
confidence: 99%
“…Hydrotalcite materials have the formula of Mg 0.667 Al 0.333 (OH) 2 (CO 3 ) 0.167 (H 2 O) 0.5 in the natural minerals. Many different layered double hydroxides and hydrotalcite materials have successfully synthesized for their applications [1,[7][8][9][10][11]. Besides MgAlCO 3 hydrotalcites, ZnAlCO 3 materials-such as hydrotalcites-are also interesting to scientists [4,5,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that these synthesized materials are capable of effectively decomposing sustainable organic compounds and dyes in water. However, some limitations remained, including (the first) the poor adsorption capacity of these materials for dyes, especially cationic dyes, (the second) the high processing costs due to the use of expensive and power-consuming equipment such as UV [3,9], Xenon [5,10,15], and halogen [16] lamps as irradiation lights, and (the third) only survey on the low concentration of dyes.…”
Section: Introductionmentioning
confidence: 99%